Osteocyte regulation of receptor activator of NF-[kappa]B ligand/osteoprotegerin in a sheep model of osteoporosis - Khassawna, Thaqif el-; Hose, Dirk; Seckinger, Anja (The American journal of pathology, 2017)
Osteoporosis induction in a sheep model by steroid administration combined with ovariectomy recapitulates decreased bone formation and substandard matrix mineralization in patients. Recently, the role of osteocytes has been frequently addressed, with focus on their role in osteoclastogenesis. However, the quantification of receptor activator of NF-κB ligand (RANKL) and osteoprotegerin (OPG) signaling in osteocytes was not studied in sheep. The current study reproduced the sheep model of osteoporosis to study the RANKL/OPG ratio correlation to the method of osteoporosis induction. We investigated the induction of osteoporosis after 8 months using 31 female merino land sheep divided into four groups: control, ovariectomy, ovariectomy with dietary limitation, and ovariectomy with dietary limitation and steroid injection. In accordance to previous reports, the present study showed trabecular thinning, higher numbers of apoptotic osteocytes, and imbalanced metabolism, leading to defective mineralization. The global RANKL/OPG ratio in the spine after 8 months of steroid and dietary treatment was not different from that of the control. Interestingly, assessment of the osteocyte-specific RANKL/OPG ratio showed that the steroid-induced osteoporosis in its late progressive phase stimulates RANKL expression in osteocytes. Sclerostin is suggested to induce RANKL expression in osteocytes. The findings of this study can contribute to further explain the success of sclerostin antibodies in treating osteoporotic patients despite increased osteocyte-expressed RANKL.